Compositional Constraints on the North Polar Cap of Mars from Gravity and Topography. Issue 15 (1st August 2019) - Ojha, Lujendra; Nerozzi, Stefano; Lewis, Kevin
Abstract: The polar ice caps are the largest reservoir of water ice on Mars. The north polar ice cap is composed of the ice‐rich north polar layered deposit (NPLD) and a lower‐lying, silicate‐rich basal unit (BU). Together, these units represent a record of Martian climate history throughout the Amazonian period. Here we place a bulk compositional constraint on the BU by modeling its gravity signature in both spatial and spectral domains using two independent approaches. We find the density of the BU to be 2007 + 493 − 445 kg/m 3, suggesting that it may contain 55 + 25% water ice. We estimate that the BU contains ~1.5‐m global equivalent layer of water making it one of the largest reservoir of water‐ice on Mars. Our compositional constraint suggests that the north pole of Mars was not only a cold trap for ices but also an aeolian trap for silicates during the Amazonian period. Plain Language Summary: The north polar cap of Mars consists of thick sheets of extremely pure ice called the north polar layered deposits and the sand‐rich basal unit. Radar data have been able to provide information on the composition of the north polar layered deposits; however, the composition of the basal unit is not entirely clear. In this study, we use gravity data of Mars to estimate the density of the basal unit. We find that the density of the basal unit is best matched by a combination of water ice and sand mixture. The relatively low density of the BU suggests that it may contain more than 50% ice. Thus, our study suggests that the basal unit may one of the largest sources of water ice on Mars. Key Points: We constrain the density of the north polar ice cap of Mars using gravity and topography data We estimate the mean density of the basal unit to be 2007 + 493 − 445 kg/m 3, suggesting that it may contain more than 50% water ice The basal unit may be the largest reservoir of water‐ice on Mars after the two polar layered deposits